Surfactant-free syntheses and pair distribution function analysis of osmium nanoparticles - Juelsholt, Mikkel; Quinson, Jonathan; Kjær, Emil T. S.; Wang, Baiyu; Pittkowski, Rebecca; Cooper, Susan R.; Kinnibrugh, Tiffany L.; Simonsen, Søren B.; Theil Kuhn, Luise; Escudero-Escribano, María; Jensen, Kirsten M. Ø. (Beilstein Journal of Nanotechnology, 2022)
A surfactant-free synthesis of precious metal nanoparticles (NPs) performed in alkaline low-boiling-point solvents has been recently reported. Monoalcohols are here investigated as solvents and reducing agents to obtain colloidal Os nanoparticles by using low-temperature (<100 °C) surfactant-free syntheses. The effect of the precursor (OsCl3 or H2OsCl6), precursor concentration (up to 100 mM), solvent (methanol or ethanol), presence or absence of a base (NaOH), and addition of water (0 to 100 vol %) on the resulting nanomaterials is discussed. It is found that no base is required to obtain Os nanoparticles as opposed to the case of Pt or Ir NPs. The robustness of the synthesis for a precursor concentration up to 100 mM allows for the performance of X-ray total scattering with pair distribution function (PDF) analysis, which shows that 1–2 nm hexagonal close packed (hcp) NPs are formed from chain-like [OsOxCly] complexes.
Keywords: metal nanoparticles; osmium; pair distribution function; surfactant-free synthesis